Paid attention : innovative advertising for a digital world - Yakob, Faris (New York : Kogan Page Inc, 2022)
"The advertising attention marketplace is a confusing and vast playi ng field where the rules have changed drastically over the last decade. Make yourself heard and win the attention of your target audience with the new edition of this ultimate guide.Paid Attention delivers new and innovative insights into advertising ideas: what they are, why they ar e evolving and how to use them in day to day strategy to ensure commerc ial stability within a changing digital landscape. Packed with real-wor ld examples of advertising campaigns such as Google, Sony and Old Spice , it provides a robust model for influencing human behaviour and toolki ts that offer best practice on brand behaviour and effective communicat ion.This second edition includes two new chapters exploring the latest evidence about attention spans and trends in online advertising, as wel l as new case studies on compelling brand ideas. In a world where being a consumer is confusing, learn to take control of the situation and ma ke yourself heard in today's crowded attention marketplace"--
Revised edition of the author's Paid attention, 2015.
Includes bibliographical references and index.
Keywords: Advertising; Branding (Marketing); Electronic commerce